The moderating role of intrinsic motivation on the relationship between toxic leadership and emotional exhaustion - Koç, Oktay; Bozkurt, Serdar; Taşdemir, Deniz Devrim; Günsel, Ayşe (Frontiers in Psychology, 2022)
Dysfunctional and destructive leadership behaviors have begun to be seen frequently in today’s business world. Likewise, toxic leadership, with incompetent supervision elements results with negative outputs for organizations and heavily for the employees. Employees may experience long-term stress in the work environment and develop emotional exhaustion, resulting in mental breakdown. Hence, this study aims to reveal the effects of toxic leadership on emotional exhaustion within the healthcare industry as a first step. Moreover, we also attempt to reveal the contingency of intrinsic motivation to lessen the reflections of toxic leadership on emotional exhaustion as a second step. Using PLS-SEM, we find that toxic leadership is positively associated with emotional exhaustion. Furthermore, our findings provide empirical evidence supporting the moderator role of intrinsic motivation on the relationship between toxic leadership and emotional exhaustion.